Spectral Flow : A Functional Analytic and Index-Theoretic Approach. - Doll, Nora. (De Gruyter Studies in Mathematics Series, 2023)
The series de Gruyter Studies in Mathematics was founded ca. 35 years ago by the late Professor Heinz Bauer and Professor Peter Gabriel. The series is devoted to the publication of monographs and high-level textbooks in mathematics, mathematical methods, and their applications. Apart from covering important areas of current interest, a major aim is to make topics of an interdisciplinary nature accessible to the non-specialist.